Pengaruh persepsi orang tua terhadap kesetaraan gender - Permata, Divia Atma (Maliki Interdisciplinary Journal, 2024)
Gender equality is a crucial concept that ensures equal access to rights, opportunities, and resources for all genders. Parents play a vital role in shaping children’s perceptions of gender equality. Children observe and imitate their parents’ behaviors, meaning that parental attitudes and actions regarding gender roles can influence their children’s views and behaviors. Parental perceptions of gender equality are influenced by education, social background, culture, and media. Parents with higher levels of education tend to have more progressive views on gender equality. Meanwhile, traditional cultures often reinforce gender stereotypes, while media can alter perceptions by portraying inclusive gender roles. Education and socialization are key to increasing parental awareness of the importance of gender equality. Educational programs and activities supported by schools and communities can help parents understand and implement gender equality values in their daily lives. With better understanding, parents can teach their children to appreciate and respect gender differences and support the achievement of their full potential without being constrained by gender stereotypes. This effort aims to create a more just and equitable generation in the future.